Evaluating distributed generation impacts with a multiobjective index - Ochoa, L. F.; Padilha-Feltrin, A.; Harrison, G. P. (Institute of Electrical and Electronics Engineers (IEEE), 2006)
Evaluating the technical impacts associated with connecting distributed generation to distribution networks is a complex activity requiring a wide range of network operational and security effects to be qualified and quantified. One means of dealing with such complexity is through the use of indices that indicate the benefit or otherwise of connections at a given location and which could be used to shape the nature of the contract between the utility and distributed generator. This paper presents a multiobjective performance index for distribution networks with distributed generation which considers a wide range of technical issues. Distributed generation is extensively located and sized within the IEEE-34 test feeder, wherein the multiobjective performance index is computed for each configuration. The results are presented and discussed.
Keywords: distributed generation (DG); distribution networks; multiobjective analysis